Economic Problems of the Leading Russian National Newspapers: Information Priorities and Language Specificity - Failevich Fattakhov, Ilgam; Rassyhovich Gazizov, Ramis (International Journal of Criminology and Sociology, 2022)
It contains the results of a study devoted to determining the role and place of economic topics in the largest federal publications in Russia. The range of issues covered in this area is wide, and reflects global and national trends, and the economy has a prominent place in the structure of publications. The study focuses on the definition of economically oriented content of publications: Rossiyskaya Gazeta and Izvestia. The authors pay attention to both structural (heading of printed elements, site navigation), and content elements (problems, language and stylistic features). The most characteristic materials on various aspects of the economy are analyzed. The increasing role of the economy, crisis in this area lead to increased demand for the mass audience in the news in this area.